# Calculator search results

Formula
Number of solution
Relationship between roots and coefficients
Graph
$y = \left ( 3 x - 1 \right ) \left ( 2 x + 3 \right )$
$y = \left ( x + 9 \right ) \left ( x + 8 \right )$
$x$Intercept
$\left ( \dfrac { 1 } { 3 } , 0 \right )$, $\left ( - \dfrac { 3 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 3 \right )$
Minimum
$\left ( - \dfrac { 7 } { 12 } , - \dfrac { 121 } { 24 } \right )$
Standard form
$y = 6 \left ( x + \dfrac { 7 } { 12 } \right ) ^ { 2 } - \dfrac { 121 } { 24 }$
$x$Intercept
$\left ( - 8 , 0 \right )$, $\left ( - 9 , 0 \right )$
$y$Intercept
$\left ( 0 , 72 \right )$
Minimum
$\left ( - \dfrac { 17 } { 2 } , - \dfrac { 1 } { 4 } \right )$
Standard form
$y = \left ( x + \dfrac { 17 } { 2 } \right ) ^ { 2 } - \dfrac { 1 } { 4 }$
$\left( 3x-1 \right) \left( 2x+3 \right) = \left( x+9 \right) \left( x+8 \right)$
$\begin{array} {l} x = 5 \\ x = - 3 \end{array}$
Find solution by method of factorization
$\left ( 3 x - 1 \right ) \left ( 2 x + 3 \right ) = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 8 } \right )$
 Move the expression to the left side and change the symbol 
$\left ( 3 x - 1 \right ) \left ( 2 x + 3 \right ) - \left ( x + 9 \right ) \left ( x + 8 \right ) = 0$
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) \color{#FF6800}{ - } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 8 } \right ) = 0$
 Expand the expression 
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 75 } = 0$
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 75 } = 0$
$acx^{2} + \left(ad + bc\right)x +bd = \left(ax + b\right)\left(cx+d\right)$
$\color{#FF6800}{ 5 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) = 0$
$\color{#FF6800}{ 5 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) = \color{#FF6800}{ 0 }$
 If the product of the factor is 0, at least one factor should be 0 
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 } \end{array}$
 Solve the equation to find $x$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 5 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{array}$
$\begin{array} {l} x = 5 \\ x = - 3 \end{array}$
Solve quadratic equations using the square root
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) = \left ( x + 9 \right ) \left ( x + 8 \right )$
 Organize the expression 
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } = \left ( x + 9 \right ) \left ( x + 8 \right )$
$6 x ^ { 2 } + 7 x - 3 = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 8 } \right )$
 Organize the expression 
$6 x ^ { 2 } + 7 x - 3 = \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 72 }$
$6 x ^ { 2 } + 7 x - 3 = \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } + 72$
 Move the expression to the left side and change the symbol 
$6 x ^ { 2 } + 7 x - 3 \color{#FF6800}{ - } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = 0$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = \color{#FF6800}{ 0 }$
 Organize the expression 
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 75 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 75 } = \color{#FF6800}{ 0 }$
 Divide both sides by the coefficient of the leading highest term 
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 15 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 15 } = \color{#FF6800}{ 0 }$
 Convert the quadratic expression on the left side to a perfect square format 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 15 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 15 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
 Organize the expression 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 16 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 16 }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \pm \sqrt{ \color{#FF6800}{ 16 } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \pm \sqrt{ \color{#FF6800}{ 16 } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 4 } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 4 } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ 1 } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \end{array}$
 Organize the expression 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 5 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{array}$
$\begin{array} {l} x = 5 \\ x = - 3 \end{array}$
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) = \left ( x + 9 \right ) \left ( x + 8 \right )$
 Organize the expression 
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } = \left ( x + 9 \right ) \left ( x + 8 \right )$
$6 x ^ { 2 } + 7 x - 3 = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 8 } \right )$
 Organize the expression 
$6 x ^ { 2 } + 7 x - 3 = \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 72 }$
$6 x ^ { 2 } + 7 x - 3 = \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } + 72$
 Move the expression to the left side and change the symbol 
$6 x ^ { 2 } + 7 x - 3 \color{#FF6800}{ - } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = 0$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = \color{#FF6800}{ 0 }$
 Organize the expression 
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 75 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 75 } = 0$
 Bind the expressions with the common factor $5$
$\color{#FF6800}{ 5 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 15 } \right ) = 0$
$\color{#FF6800}{ 5 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 15 } \right ) = \color{#FF6800}{ 0 }$
 Divide both sides by $5$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 15 } = \color{#FF6800}{ 0 }$
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 2 \right ) \pm \sqrt{ \left ( - 2 \right ) ^ { 2 } - 4 \times 1 \times \left ( - 15 \right ) } } { 2 \times 1 }$
 Simplify Minus 
$x = \dfrac { 2 \pm \sqrt{ \left ( - 2 \right ) ^ { 2 } - 4 \times 1 \times \left ( - 15 \right ) } } { 2 \times 1 }$
$x = \dfrac { 2 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 15 \right ) } } { 2 \times 1 }$
 Remove negative signs because negative numbers raised to even powers are positive 
$x = \dfrac { 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 1 \times \left ( - 15 \right ) } } { 2 \times 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 1 \times \left ( - 15 \right ) } } { 2 \times 1 } }$
 Organize the expression 
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm \sqrt{ 64 } } { 2 \times 1 } }$
$x = \dfrac { 2 \pm \sqrt{ \color{#FF6800}{ 64 } } } { 2 \times 1 }$
 Organize the part that can be taken out of the radical sign inside the square root symbol 
$x = \dfrac { 2 \pm \color{#FF6800}{ 8 } } { 2 \times 1 }$
$x = \dfrac { 2 \pm 8 } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
 Multiplying any number by 1 does not change the value 
$x = \dfrac { 2 \pm 8 } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 \pm 8 } { 2 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 + 8 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 2 - 8 } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 2 } \color{#FF6800}{ + } \color{#FF6800}{ 8 } } { 2 } \\ x = \dfrac { 2 - 8 } { 2 } \end{array}$
 Add $2$ and $8$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 10 } } { 2 } \\ x = \dfrac { 2 - 8 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 10 } { 2 } } \\ x = \dfrac { 2 - 8 } { 2 } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 5 } { 1 } } \\ x = \dfrac { 2 - 8 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 5 } { 1 } } \\ x = \dfrac { 2 - 8 } { 2 } \end{array}$
 Reduce the fraction to the lowest term 
$\begin{array} {l} x = \color{#FF6800}{ 5 } \\ x = \dfrac { 2 - 8 } { 2 } \end{array}$
$\begin{array} {l} x = 5 \\ x = \dfrac { \color{#FF6800}{ 2 } \color{#FF6800}{ - } \color{#FF6800}{ 8 } } { 2 } \end{array}$
 Subtract $8$ from $2$
$\begin{array} {l} x = 5 \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 6 } } { 2 } \end{array}$
$\begin{array} {l} x = 5 \\ x = \color{#FF6800}{ \dfrac { - 6 } { 2 } } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = 5 \\ x = \color{#FF6800}{ \dfrac { - 3 } { 1 } } \end{array}$
$\begin{array} {l} x = 5 \\ x = \dfrac { - 3 } { \color{#FF6800}{ 1 } } \end{array}$
 If the denominator is 1, the denominator can be removed 
$\begin{array} {l} x = 5 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{array}$
 2 real roots 
Find the number of solutions
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) = \left ( x + 9 \right ) \left ( x + 8 \right )$
 Organize the expression 
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } = \left ( x + 9 \right ) \left ( x + 8 \right )$
$6 x ^ { 2 } + 7 x - 3 = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 8 } \right )$
 Organize the expression 
$6 x ^ { 2 } + 7 x - 3 = \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 72 }$
$6 x ^ { 2 } + 7 x - 3 = \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } + 72$
 Move the expression to the left side and change the symbol 
$6 x ^ { 2 } + 7 x - 3 \color{#FF6800}{ - } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = 0$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } + 7 x - 3 \color{#FF6800}{ - } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } - 17 x - 72 = 0$
 Calculate between similar terms 
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } + 7 x - 3 - 17 x - 72 = 0$
$5 x ^ { 2 } + \color{#FF6800}{ 7 } \color{#FF6800}{ x } - 3 \color{#FF6800}{ - } \color{#FF6800}{ 17 } \color{#FF6800}{ x } - 72 = 0$
 Calculate between similar terms 
$5 x ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } - 3 - 72 = 0$
$5 x ^ { 2 } - 10 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = 0$
 Find the sum of the negative numbers 
$5 x ^ { 2 } - 10 x \color{#FF6800}{ - } \color{#FF6800}{ 75 } = 0$
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 75 } = \color{#FF6800}{ 0 }$
 Determine the number of roots using discriminant, $D=b^{2}-4ac$ from quadratic equation, $ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 10 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 75 } \right )$
$D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 10 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 5 \times \left ( - 75 \right )$
 Remove negative signs because negative numbers raised to even powers are positive 
$D = 10 ^ { 2 } - 4 \times 5 \times \left ( - 75 \right )$
$D = \color{#FF6800}{ 10 } ^ { \color{#FF6800}{ 2 } } - 4 \times 5 \times \left ( - 75 \right )$
 Calculate power 
$D = \color{#FF6800}{ 100 } - 4 \times 5 \times \left ( - 75 \right )$
$D = 100 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 75 } \right )$
 Multiply the numbers 
$D = 100 + \color{#FF6800}{ 1500 }$
$D = \color{#FF6800}{ 100 } \color{#FF6800}{ + } \color{#FF6800}{ 1500 }$
 Add $100$ and $1500$
$D = \color{#FF6800}{ 1600 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 1600 }$
 Since $D>0$ , the number of real root of the following quadratic equation is 2 
 2 real roots 
$\alpha + \beta = 2 , \alpha \beta = - 15$
Find the sum and product of the two roots of the quadratic equation
$\left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) = \left ( x + 9 \right ) \left ( x + 8 \right )$
 Organize the expression 
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } = \left ( x + 9 \right ) \left ( x + 8 \right )$
$6 x ^ { 2 } + 7 x - 3 = \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 9 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 8 } \right )$
 Organize the expression 
$6 x ^ { 2 } + 7 x - 3 = \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 72 }$
$6 x ^ { 2 } + 7 x - 3 = \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } + 72$
 Move the expression to the left side and change the symbol 
$6 x ^ { 2 } + 7 x - 3 \color{#FF6800}{ - } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = 0$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } + 7 x - 3 \color{#FF6800}{ - } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } - 17 x - 72 = 0$
 Calculate between similar terms 
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } + 7 x - 3 - 17 x - 72 = 0$
$5 x ^ { 2 } + \color{#FF6800}{ 7 } \color{#FF6800}{ x } - 3 \color{#FF6800}{ - } \color{#FF6800}{ 17 } \color{#FF6800}{ x } - 72 = 0$
 Calculate between similar terms 
$5 x ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } - 3 - 72 = 0$
$5 x ^ { 2 } - 10 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = 0$
 Find the sum of the negative numbers 
$5 x ^ { 2 } - 10 x \color{#FF6800}{ - } \color{#FF6800}{ 75 } = 0$
$\color{#FF6800}{ 5 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 75 } = \color{#FF6800}{ 0 }$
 In the quadratic equation $ax^{2}+bx+c=0$ , if the two roots are $\alpha, \beta$ , then it is $\alpha + \beta =-\dfrac{b}{a}$ , $\alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 10 } { 5 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { - 75 } { 5 } }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 10 } { 5 } } , \alpha \beta = \dfrac { - 75 } { 5 }$
 Solve the sign of a fraction with a negative sign 
$\alpha + \beta = \color{#FF6800}{ \dfrac { 10 } { 5 } } , \alpha \beta = \dfrac { - 75 } { 5 }$
$\alpha + \beta = \color{#FF6800}{ \dfrac { 10 } { 5 } } , \alpha \beta = \dfrac { - 75 } { 5 }$
 Reduce the fraction 
$\alpha + \beta = \color{#FF6800}{ 2 } , \alpha \beta = \dfrac { - 75 } { 5 }$
$\alpha + \beta = 2 , \alpha \beta = \color{#FF6800}{ \dfrac { - 75 } { 5 } }$
 Reduce the fraction 
$\alpha + \beta = 2 , \alpha \beta = \color{#FF6800}{ - } \color{#FF6800}{ 15 }$
 그래프 보기 
Graph
Solution search results